2011
DOI: 10.1002/adfm.201100763
|View full text |Cite
|
Sign up to set email alerts
|

High‐Energy Al/CuO Nanocomposites Obtained by DNA‐Directed Assembly

Abstract: Over the next few years, it is expected that new, energetic, multifunctional materials will be engineered. There is a need for new methods to assemble such materials from manufactured nanopowders. In this article, we demonstrate a DNA-directed assembly procedure to produce highly energetic nanocomposites by assembling Al and CuO nanoparticles into micrometersized particles of an Al/CuO nanocomposite, which has exquisite energetic performance in comparison with its physically mixed Al/CuO counterparts. Using 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
109
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(111 citation statements)
references
References 45 publications
2
109
0
Order By: Relevance
“…In our previous study, we also found a significant increase in reactivity when oppositely charged fuel and oxidizer nanoparticles were assembled [25]. More recently, Rossi et al demonstrated a DNA-directed assembly procedure to produce highly energetic nanocomposites by assembling Al and CuO nanoparticles into microparticles [32]. All these studies show the same general result, that intimate interfacial contact results in high reactivity.…”
Section: Introductionmentioning
confidence: 76%
“…In our previous study, we also found a significant increase in reactivity when oppositely charged fuel and oxidizer nanoparticles were assembled [25]. More recently, Rossi et al demonstrated a DNA-directed assembly procedure to produce highly energetic nanocomposites by assembling Al and CuO nanoparticles into microparticles [32]. All these studies show the same general result, that intimate interfacial contact results in high reactivity.…”
Section: Introductionmentioning
confidence: 76%
“…Nanothermites also open the perspective to fabricate smaller weapon systems or higher lethality weapon. Moreover, compared to conventional explosives, one asset of nanoenergetic materials is the possible adjustment of the energy density, power release and pressure generation by a suitable choice of fuels, oxidizers, material geometries and reactant compaction [3,[14][15][16][17][18][19][20][21][22]. Until recently, very few reports have considered the dynamic pressures developed by the gas expansion during nanothermites reactions [11,[23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…MICs are preparedb ym ixing nanoparticleso fm etallic oxides (MoO 3 ,C uO, Fe 2 O 3 ,a nd Bi 2 O 3 )w ith aluminum [1][2][3][4].S everal methods have been employed to realizeM ICs, including physical mixing, sol-gel,s putteringo fm ultilayer foils, aero-gel, molecular self-assembly [5][6][7][8][9].W hile each method has its merits,s everal disadvantages have also been obtained. Thus, developing novel, facile, and scalable methods to synthesize MICs with homogeneityi sa ni mportant endeavor.…”
mentioning
confidence: 99%